Apoplastic effector candidates of a foliar forest pathogen trigger cell death in host and non-host plants - Hunziker, Lukas; Tarallo, M.; Gough, K.; Guo, M.; Hargreaves, C.; Loo, T.S.; McDougal, R.L.; Mesarich, C.H.; Bradshaw, R.E. (NATURE PORTFOLIO, 2021)
Forests are under threat from pests, pathogens, and changing climate. A major forest pathogen worldwide is the hemibiotroph Dothistroma septosporum, which causes dothistroma needle blight (DNB) of pines. While D. septosporum uses effector proteins to facilitate host infection, it is currently unclear whether any of these effectors are recognised by immune receptors to activate the host immune system. Such information is needed to identify and select disease resistance against D. septosporum in pines. We predicted and investigated apoplastic D. septosporum candidate effectors (DsCEs) using bioinformatics and plant-based experiments. We discovered DsCEs that trigger cell death in the angiosperm Nicotiana spp., indicative of a hypersensitive defence response and suggesting their recognition by immune receptors in non-host plants. In a first for foliar forest pathogens, we developed a novel protein infiltration method to show that tissue-cultured pine shoots can respond with a cell death response to a DsCE, as well as to a reference cell death-inducing protein. The conservation of responses across plant taxa suggests that knowledge of pathogen–angiosperm interactions may also be relevant to pathogen–gymnosperm interactions. These results contribute to our understanding of forest pathogens and may ultimately provide clues to disease immunity in both commercial and natural forests.